Biosensors for the detection of respiratory viruses: A review (2020)
The recent events of outbreaks related to different respiratory viruses in the past few years, exponentiated by the pandemic caused by the coronavirus disease 2019 (COVID-19), reported worldwide caused by SARS-CoV-2, raised a concern and increased the search for more information on viruses-based diseases. The detection of the virus with high specificity and sensitivity plays an important role for an accurate diagnosis. Despite the many efforts to identify the SARS-CoV-2, the diagnosis still relays on expensive and time-consuming analysis. A fast and reliable alternative is the use of low-cost biosensor for in loco detection. This review gathers important contributions in the biosensor area regarding the most current respiratory viruses, presents the advances in the assembly of the devices and figures of merit. All information is useful for further biosensor development for the detection of respiratory viruses, such as for the new coronavirus.